Strategic Choice and Performance in Late Movers: Influence of the Top Management Team's External Ties - Yoo, Jae Wook; Reed, Richard; Shin, Shung Jae; Lemak, David J. (Journal of Management Studies, 2009)
abstractThis work examines how the strategic choice and performance of late movers are influenced by the top management team's external ties, inside and outside the firm's industry. Using a multiyear sample of firms from the computer industry, we found that intra‐industry trade‐association ties of top managers led to the adoption of a resource‐imitation strategy by late movers while extra‐industry importation and professional‐association ties led to the adoption of a resource‐substitution strategy. We also found that trade association ties had a negative effect on the performance of late movers using resource‐substitution, while top managers' service on other firms' boards had a positive influence on the performance of those firms. Our findings not only confirm the importance of the role of fit in strategy and performance, but they also highlight the importance of the management and control of boundary‐spanning activities.